Peran Perempuan dalam Masyarakat terhadap Penempatan Anggota Legislatif di Komisi DPR RI Periode 2019-2024 - Sari, Anggita Dita; Octaviana, Arvi; Kamila, Devina Cahya; Permatasari, Nian Puspita; Irawan, Tasya Fatah Putri; Hadji, Kuswan (Judge : Jurnal Hukum, 2025)
Indonesia as a democratic country upholds equal rights for all citizens to participate in politics including women. However, women still face discrimination in accessing strategic positions in state institutions especially in the legislature. Even though there has been an increase in women's representation in the Indonesian House of Representatives (DPR) in the 2019-2024 period, challenges remain especially in their placement in commissions which are important policy-making arenas. This research examines the distribution of women's roles in DPR commissions, the impact of this representation on policy, and how social factors such as class, ethnicity and education influence their opportunities in the legislative body. This study aims to provide insight into the contribution of women in policy making and gender dynamics in parliament which is expected to support the development of more inclusive policies and a gender perspective in Indonesia.